Chemical characterization and potential use of reptile fat from sustainable programs - Leiva, Pamela M. L.; Valli, Florencia E.; Piña, Carlos I.; González, Marcela A.; Simoncini, Melina S. (Ethnobiology and Conservation, 2022)
Reptile meats and fats are used for their medicinal properties and nutritional values ​​perceived through the culture of native peoples, though often with no scientific basis. Providing scientific information about potential medicinal and nutritional use of reptile fats would be a strategy for the full use of wild animals, supporting the sustainable use and conservation of biodiversity. The objective of this study was to characterize and chemically compare the fat and oil of individuals of Argentine Black and white tegu (Salvator merianae) and Broad-snouted caiman (Caiman latirostris) from sustainable use and conservation programs. In addition, we evaluated the microbiological characteristics and the antimicrobial activity of the oils obtained by different methods. We used two methodologies to obtain oils, one by fusion extraction and the other by drying-decantation (traditional hunter’s method). We obtained the chemical and microbiological characterization of fat and oil of latirostris and S. merianae. All the oil samples presented less than 10 CFU/ml of all the microorganisms tested. C. latirostris and S. merianae oil showed nutritional quality parameters that indicate its potential use. Furthermore, S. merianae oil showed antimicrobial activity against Staphylococcus aureus and Candidas tropicalis. No inhibition occurs for the rest of the microorganisms analyzed. C. latirostris oil did not show antimicrobial activity, although the lipid profile does indicate some anti-inflammatory potential. This study demonstrates the potential application of the tested oils and confirms the pharmacological basis for the traditional therapeutic use of S. merianae oil.